Effectiveness of segmentation, positioning and the marketing initiatives of museums in Singapore : a case study on the Singapore Art Museum and the Asian Civilizations Museum - Loh, Corine Cheng Ya (2010)
The report is aimed at revealing the relationship among three critical aspects of a museum, namely Segmentation, Positioning and Marketing Initiatives (SPM). A SPM gear model is being adopted to provide a pictorial illustration of how these three aspects are linked and should move congruently to drive the success of museums in Singapore. An analysis of the findings shows the effectiveness of how the current SPM, of the Singapore Art Museum (SAM) and Asian Civilisations Museum (ACM), support and reinforce each other; recommendations are also proposed to improve this effectiveness. Ultimately, this study serves to assist museum managers in their marketing strategies, as they prepare to face challenges in serving the changing needs of customers and the dynamic environments.